2021
DOI: 10.3390/jcm10091907
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Exploration of Plasma Biomarkers of Alzheimer’s Disease in Down Syndrome: Early Data from the Longitudinal Investigation for Enhancing Down Syndrome Research (LIFE-DSR) Study

Abstract: With improved healthcare, the Down syndrome (DS) population is both growing and aging rapidly. However, with longevity comes a very high risk of Alzheimer’s disease (AD). The LIFE-DSR study (NCT04149197) is a longitudinal natural history study recruiting 270 adults with DS over the age of 25. The study is designed to characterize trajectories of change in DS-associated AD (DS-AD). The current study reports its cross-sectional analysis of the first 90 subjects enrolled. Plasma biomarkers phosphorylated tau prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…Activation of astrocytes and microglia, the secretion of inflammatory cytokines (e.g., IL-1, IL-6, and TNFα), and acute phase proteins are observed in both the brains and blood of people with DS, indicating an “inflammatory endophenotype” (Petersen and O’Bryant, 2019 ). In a cross-sectional analysis of people with DS, plasma glial fibrillary acidic protein (GFAP), a marker of astrogliosis, was found to increase starting in their mid-40s (Hendrix et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of astrocytes and microglia, the secretion of inflammatory cytokines (e.g., IL-1, IL-6, and TNFα), and acute phase proteins are observed in both the brains and blood of people with DS, indicating an “inflammatory endophenotype” (Petersen and O’Bryant, 2019 ). In a cross-sectional analysis of people with DS, plasma glial fibrillary acidic protein (GFAP), a marker of astrogliosis, was found to increase starting in their mid-40s (Hendrix et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher plasma levels of GFAP are correlated with lower measures of episodic memory and microstructural integrity in AD, MCI, and also in healthy aged donors (Bettcher et al, 2021 ). As discussed, people with DS also have increasing levels of plasma GFAP starting in their mid-40s (Hendrix et al, 2021 ). Thus, although initially thought to be a secondary effect of aberrant protein accumulation, changes in the innate immune system and neuroinflammation are now thought to be a core, early feature of both DS and AD that interface with, and may contribute to, clinical manifestations of cognitive disorders and decline (Lucin and Wyss-Coray, 2009 ; Heneka et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent improvements in medical care have contributed to the increased longevity of individuals with DS, and advancements in diagnostic biomarkers have facilitated studies of key questions regarding the interconnected clinical and neuropathological features that develop with age in DS (Neale et al, 2018 ; Handen et al, 2020 ; Head and Ances, 2020 ; Petersen et al, 2020 , 2021 ; Rafii et al, 2020 ; Hendrix et al, 2021 ). Positron emission tomography (PET) studies using Pittsburgh Compound-B ( 11 C-PiB) and related amyloid-binding radiopharmaceuticals provide insight into regional distributions and temporal changes in Aβ pathology in living people with AD (Klunk et al, 2004 ; Rowe et al, 2007 ; Cohen et al, 2012 ; Mathis et al, 2017 ; Villemagne et al, 2021 ) and this technology is being applied increasingly to studies of individuals with DS (Landt et al, 2011 ; Handen et al, 2012 ; Hartley et al, 2014 , 2017 , 2020 ; Annus et al, 2016 , 2017 ; Lao et al, 2016 , 2017 , 2018 ; Cole et al, 2017 ; Cohen et al, 2018 ; Neale et al, 2018 ; Mak et al, 2019a , b ; Mihaila et al, 2019 ; Tudorascu et al, 2019 , 2020 ; Wilson et al, 2019 ; Cody et al, 2020 ; Zammit et al, 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical cohorts in the US and Europe are working together to determine the best panels of blood biomarkers for adults with DS related to dementia. In Hendrix et al’s (2021) [ 4 ] paper, the Longitudinal Investigation for Enhancing Down Syndrome Research (LIFE-DSR) Study reported early findings from a natural history study of adults with DS in the USA. The LIFE-DSR study consists of 11 sites, who are collectively recruiting 270 individuals with DS over the age of 25.…”
mentioning
confidence: 99%